2016
DOI: 10.4193/rhino15.120
|View full text |Cite
|
Sign up to set email alerts
|

Primary school children often underestimate their nasal obstruction

Abstract: Background: No consensus has ever been reached about the correlation between nasal resistance and the subjective sensation of nasal patency. The aim of the present study was to better de ne whether primary school and secondary school aged children correctly estimate their nasal obstruction. Materials and methods: Two hundred eighty four children (168 males and 116 female) aged between 6 and 14 years (9.5+2.9 years) affected by Pediatric Allergic Rhinitis underwent Rhinomanometry and they were considered as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Other studies found the same reduction in nNO in adults and children with allergic rhinitis treated with nasal corticosteroids [44]. At a molecular level, the corticosteroid effect is explained by the inhibition of the transcription nuclear factor (NF-kB) that normally mediates the transcription of the iNOS gene [45].…”
Section: Applications Of Nno In Other Respiratory Inflammatory Diseasesmentioning
confidence: 79%
“…Other studies found the same reduction in nNO in adults and children with allergic rhinitis treated with nasal corticosteroids [44]. At a molecular level, the corticosteroid effect is explained by the inhibition of the transcription nuclear factor (NF-kB) that normally mediates the transcription of the iNOS gene [45].…”
Section: Applications Of Nno In Other Respiratory Inflammatory Diseasesmentioning
confidence: 79%